International Handbook of Urban Education
XLVI, 1267 p.
Keywords: It is evident that urban education has become the central focus of educators at the present time. In the U.S., for example, almost one third of all school age children attend schools in large urban school districts. It is in these urban schools where the diversity of cultures and languages is highest and where student learning is most problematic. What has emerged from recent work to improve urban schools is the insight that there is no one-size-fits-all panacea. Rather, we have discovered that the local context shapes, in critically important ways, what will be effective at the school level. The universality of the problematics with urban education, together with the importance of understanding the local, or situated, context of improvement interventions, brings into sharp focus the importance and timeliness of an undertaking like the International Handbook of Urban Education. An important focus of the International Handbook of Urban Education will be the interrogation of both the social and political factors that lead to different problem posing and subsequent solutions within each region. An important question to be answered, for example, is what it takes in terms of resources, political will and policy actions to improve urban education.